Clinically oriented anatomy - Keith L. Moore (Lippincott Williams & Wilkins, 1999)
Originally published in 1980, this text, now in its fifth edition, has had a leisurely update schedule so that changes could be thoughtfully planned. This time-tested text is intended as a text/resource for medical, dental, physical therapy, and other health sciences students undergoing their first exposure to the topic. The new edition, four years in the works, includes new clinical correlations and summaries; a more practical approach to the musculoskeletal system emphasizing the action and use of muscles in daily activities; new color photos for surface anatomy; medical imaging information; interactive case studies and multiple-choice questions; and new art. The two included CD-ROMs contain interactive case studies; USMLE-style review questions; and 3-D models of MRI images, which generate layered, rotatable anatomical illustrations. The work of authors Moore (emeritus, U. of Toronto) and Dalley (Vanderbilt U. School of Medicine) was augmented by contributions from Anne M.R. Agur (U. of Toronto).